Melodrive [videorecording (DVD)] - Wenman-Hyde Oscar; Collins, Michelle, 1962-; Arnold, Mark, 1957-; Wake, Matt; Wunna, Chrissie; During, Christine (Burning Bulb Productions, 2025)
After separating from his wife due to an emotional affair, Ethan, a homeward-bound musician, goes on a road trip to get back in touch with his roots, but after bumping into his high school sweetheart, Zoey, his feelings become even more off balance. They end up going on a wild adventure through North Devon that makes them both feel like teenagers again. Sexual tension that never got a chance to blossom taunts its power, and their chemistry is evident as they journey through new and old feelings. However, it soon becomes clear that both of them are just a means for an escape.